Genetic background determines phenotypic severity of the Plp rumpshaker mutation - Al-Saktawi, Khalid; Klugmann, Matthias; Schneider, Armin; Nave, Klaus-Armin (Journal of neuroscience research, 2003)
The rumpshaker mutation of the proteolipid protein (Plp) gene causes dysmyelination in man and mouse. We show that the phenotype in the mouse depends critically on the genetic background in which the mutation is expressed. On the C3H background there is normal longevity whereas changing to a C57BL/6 strain results in seizures and death at around postnatal day 30. The more severe phenotype is associated with less myelin and reduced levels of major myelin proteins. There are also more apoptotic cells, including oligodendrocytes, increased numbers of proliferating cells, increased numbers of NG2+ oligodendrocyte progenitors and increased microglia compared to the milder phenotype. The number of mature oligodendrocytes is similar to wild-type in both strains of mutant, however, suggesting that increased oligodendrocyte death is matched by increased generation from progenitors. The dichotomy of phenotype probably reflects the influence of modifying loci. The localization of these putative modifying genes and their mode of action remain to be determined. © 2003 Wiley-Liss, Inc.
Gesehen am 06.09.2017